Hydro Economic Asymmetries and Common‐Pool Overdraft in Transboundary Aquifers. Issue 11 (21st November 2022) - Mullen, Connor; Müller, Marc F.; Penny, Gopal; Hung, Fengwei; Bolster, Diogo
Abstract: The common‐pool nature of groundwater resources creates incentives to over pump that contribute to their rapid global depletion. In transboundary aquifers, users are separated by a territorial border and might face substantially different economic and hydrogeologic conditions that can alternatively dampen or amplify incentives to over pump. We develop a theoretical model that couples principles of game theory and groundwater flow to capture the combined effect of well locations and user asymmetries on pumping incentives. We find that heterogeneities across users (here referred to as asymmetries) in terms of either energy cost, groundwater profitability or aquifer response tend to dampen incentives to over pump. However, combinations of two or more types of asymmetry can substantially amplify common‐pool overdraft, particularly when the same user simultaneously faces comparatively higher costs (or aquifer response) and profitability. We use this theoretical insight to interpret the emergence of the Disi agreement between Saudi Arabia and Jordan in association with the Disi‐Amman water pipeline. By using bounded non‐dimensional parameters to encode user asymmetries and groundwater connectivity, the theory provides a tractable generalized framework to understand the premature depletion of shared aquifers, whether transboundary or not. Key Points: Economic and hydrogeologic differences between users affect common‐pool externalities in shared aquifers When combined, asymmetries in energy cost, groundwater profitability and aquifer response can exacerbate incentives to overpump Changing asymmetry conditions might have facilitated the world's first distance‐based groundwater treaty